An overview on bamboo culm flattening - Fang, Chang-Hua; Jiang, Ze-Hui; Sun, Zheng-Jun; Liu, Huan-Rong; Zhang, Xiu-Biao; Zhang, Rong; Fei, Ben-Hua (Construction & building materials, 2018)
•Flattening technologies offer a novel way to better use bamboo resource.•The main difficulties for bamboo culm flattening are explained.•The possible solutions for overcoming the difficulties are analyzed.•Some examples of bamboo culm flattening process are introduced. Bamboo is an abundant, sustainable resource in the tropics and subtropics. Owing to faster growth, shorter rotation and higher mechanical strength compared with other species, bamboo, as a supplement to timber, has gained increasing attention for its economic and environmental values over the last three decades. Due to the hollow cylindrical shape of bamboo culms, it is not possible to get large flat surface board directly by sawing or cutting. Research and many novel technologies on bamboo culm flattening have been reported and attempted during the last decades. This paper synthesizes the knowledge and gives an overview on bamboo culm flattening in an effort to inspire researchers and entrepreneurs to further improve and spread the technologies for better using this abundant biomass resource.